ANALISIS HUBUNGAN TINGKAT PERKEMBANGAN WILAYAH DAN POTENSI RISIKO BENCANA DI KAWASAN BENCANA LUMPUR LAPINDO KABUPATEN SIDOARJO - , MOCH SHOFWAN ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study aims to assess the characteristics and spatial distribution patterns of regional growth rate potential, determine the characteristics and spatial distribution patterns of potential disaster risk level, analyze and develop models of the relationship between the level of development and potential for disaster risk. This study used a descriptive-analytic quantitative approach based on analysis of secondary data of village potency, sub-district in the figures, and field observations. The scope of the study area includes the entire village in Porong district, Jabon district, and the Tanggulangin district which is the total number is 53 villages. There are two groups of research variables, namely the variable of the region growth and variable of disaster risk. Data analysis on regional growth rate is performed by scaling technique